Features of quality of life formation in children with visual impairments - L. I. Denysiuk (Zaporozhye State Medical University, 2024)
The relevance of the study is determined by the importance of complete healthy visual perception for quality of life and productivity in childhood. Prognostic calculations by international experts indicate increasing trends in the prevalence of ophthalmic pathology, with projections suggesting that by 2050, practically one-third of the world's population will have visual impairments, the vast majority of which are diagnosed in childhood. Aim. To study changes in the quality of life of children of different ages, its components, which continue to form during childhood under the influence of diagnosed ophthalmic pathology. Materials and methods. We analyzed the results of a sociological study using adapted versions of the standardized Children's Visual Function Questionnaire (CVFQ). Research methods included: medical-statistical, analytical-synthetic, sociological survey. The medical-statistical method involved calculating the standard deviation (σ - sigma) and standardized values of life quality assessment components (according to the CVFQ standardized questionnaire processing instructions). Results. The sections of CVFQ cover six main categories of children's quality of life: self-perception of general health status; self-assessment of vision; skills; personality status; support and family impact; treatment-related restrictions. In total, the adapted questionnaire version for children up to 3 years old contained 35 questions, and for children older than 3 years old, 40 questions. The main group included 788 individuals (of which 380 (48.2 %) had children under 3 years old and 408 (51.8 %) had children over 3 years old). The control group included 590 individuals (260 (44.1 %) had children under 3 years old and 330 (55.9 %) had children over 3 years old). The research results prove the prospects of implementing medical-preventive strategies in providing primary and specialized ophthalmic medical care, considering the significant impact of ophthalmic pathology on the formation of quality of life components in children of different ages. It is proven that the prevalence of ophthalmic pathology increases with the age of children. Conclusions. The significant medical and social importance of visual function disorders at different ages potentially threatens disability, socialization disorders, and productivity of ophthalmic patients. The growing medical and social significance of eye diseases nowadays imposes updated requirements for organizing the provision of ophthalmic care to various segments of the population.